Calculated globulin (CG) as a screening test for antibody deficiency. (September 2014) - Jolles, S.; Borrell, R.; Zouwail, S.; Heaps, A.; Sharp, H.; Moody, M.; Selwood, C.; Williams, P.; Phillips, C.; Hood, K.; Holding, S.; El Shanawany, T.
Summary Calculated globulin (total protein – albumin) is usually tested as part of a liver function test profile in both primary and secondary care and determines the serum globulin concentration, of which immunoglobulins are a major component. The main use hitherto of calculated globulin is to detect paraproteins when the level is high. This study investigated the potential to use low levels of calculated globulin to detect antibody deficiency. Serum samples with calculated globulin cut‐off < 18 g/l based on results of a pilot study were collected from nine hospitals in Wales over a 12‐month period. Anonymized request information was obtained and the samples tested for immunoglobulin levels, serum electrophoresis and, if appropriate, immunofixation. A method comparison for albumin measurement using bromocresol green and bromocresol purple was undertaken. Eighty‐nine per cent (737 of 826) samples had an immunoglobulin (Ig)G level of < 6 g/l using the bromocresol green methodology with a cut‐off of < 18 g/l, and 56% (459) had an IgG of < 4 g/l. Patients with both secondary and primary antibody deficiency were discovered and serum electrophoresis and immunofixation showed that 1·2% (10) had previously undetected small paraproteins associated with immune‐paresis. Using bromocresol purple, 74% of samples had an IgG of < 6 g/l using a cut‐off of < 23 g/l. Screening using calculated globulin with defined cut‐off values detects both primary and secondary antibody deficiency and new paraproteins associated with immune‐paresis. It is cheap, widely available and under‐utilized. Antibody‐deficient patients have been discovered using information from calculated globulin values, shortening diagnostic delay and time to treatment with immunoglobulin replacement therapy.